Biodiversity of brachyuran crabs (Crustacea : Decapoda) from non-consolidated sublittoral bottom on the northern coast of São Paulo State, Brazil - Bertini, G.; Fransozo, A.; De Mel, GAS (Kluwer Academic Publ, 2004)
The brachyuran community of the coast of São Paulo State is represented by about 188 species of crabs inhabiting different kinds of coastal marine environments. The biodiversity of brachyurans found on non-consolidated sublittoral bottom was investigated. The Ubatuba region (Ubatumirim, Ubatuba and Mar Virado bays, Couves and Mar Virado Islands, offshore region) was sampled for 3 years (1998-2000), at depths of 2-40 m. All sampling was performed using a fishing boat equipped with two double-rig nets. We collected 79 brachyuran species representing 9 superfamilies (4 Dromioidea, 1 Homoloidea, 2 Calappoidea, 5 Leucosioidea, 20 Majoidea, 7 Parthenopoidea, 17 Portunoidea, 18 Xanthoidea, and 5 Pinnotheroidea) and 41 genera. Ubatuba bay showed the greatest species richness with 50 species, followed by Ubatumirim with 45 and Mar Virado with 29. The number of species collected represents about 57% of the known species of crabs already reported for the shore of São Paulo State. It is worth noticing that this percentage is restricted only to non-consolidated sublittoral bottom. This fact indicates a great biodiversity of the habitat in this studied region, probably one to the diversity of habitat types present in the bays.
Keywords: brachyura crabs; Brazil; checklist; composition; Crustacea